„CHILDREN OF THE EMPIRE…” – POSTCOLONIAL CHARACTER OF THE UKRAINIAN CHILDREN’S BOOK AND PRESS MARKET - Świetlicki, Mateusz (Porównania, 2014)
Children’s literature was one of the most important tools in the process of creating homo sovieticus. After 1991, Ukrainians faced the problem of desovietizing the literary canon. The book market started to change: many translations of world bestsellers appeared, as well as a number of Ukrainian novels for young readers. In the Ukrainian academia too little attention is paid to studying the importance of literature for children and youth, which is one of the key elements in the formation of post-colonial identities. This article contains an overview of the Ukrainian children’s book and press market.